1978
DOI: 10.1042/bj1710357
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet difference-spectroscopic studies of substrate and inhibitor binding to Lactobacillus casei dihydrofolate reductase

Abstract: The u.v. difference spectra generated when methotrexate, trimethoprim or folate bind to Lactobacillus casei dihydrofolate reductase were analysed. The difference spectrum produced by methotrexate binding is shown to consist of three components: (a) one closely resembling that observed on protonation of methotrexate, reflecting an increased degree of protonation on binding; (b) a pH-independent contribution corresponding to a 40nm shift to longer wavelengths of a single absorption band of methotrexate; (c) a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In contrast, direct interaction between the side-chain carboxylate of E30 in rhDHFR or D27 in ecDHFR and either N 5 or N 8 of substrate might instead result in a stable charge-mediated hydrogen bond, thus interfering with charge delocalization to the adjacent carbon atom. Just such a strong hydrogen bond is seen in complexes of the tightbinding inhibitor methotrexate with clDHFR (Subramanian & Kaufman, 1978), bovine DHFR (Cocco et al, 1983), ecDHFR (Schlegel et al, 1981;Bolin et al, 1982), and lcDHFR (Hood & Roberts, 1978;Cocco et al, 1981;Bolin et al, 1982). To study the role of the carboxylic acid group, a site-directed mutant of ecDHFR was constructed, replacing D27 with asparagine (D27N) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, direct interaction between the side-chain carboxylate of E30 in rhDHFR or D27 in ecDHFR and either N 5 or N 8 of substrate might instead result in a stable charge-mediated hydrogen bond, thus interfering with charge delocalization to the adjacent carbon atom. Just such a strong hydrogen bond is seen in complexes of the tightbinding inhibitor methotrexate with clDHFR (Subramanian & Kaufman, 1978), bovine DHFR (Cocco et al, 1983), ecDHFR (Schlegel et al, 1981;Bolin et al, 1982), and lcDHFR (Hood & Roberts, 1978;Cocco et al, 1981;Bolin et al, 1982). To study the role of the carboxylic acid group, a site-directed mutant of ecDHFR was constructed, replacing D27 with asparagine (D27N) .…”
Section: Discussionmentioning
confidence: 93%
“…That a similarity between the pH difference spectrum in solution and the binding difference spectrum indicates proton uptake by a ligand has been demonstrated by calorimetric measurements on methotrexate binding to clDHFR (Subramanian & Kaufman, 1978). In contrast, there is no such evidence for protonation when folate binds to rhDHFR (spectra not shown), clDHFR (Subramanian & Kaufman, 1978), ecDHFR (Poe et al, 1974), lcDHFR (Hood & Roberts, 1978), or bacteriophage T4 specific DHFR (Erickson & Mathews, 1972). Moreover, a semiempirical calculation of the heats of formation of both N 1 and N8 protonated 5-deaza-6-methylpteridine (an analogue of 5-deazafolate lacking the pABG moiety) by the AM1 method (Dewar et al, 1985) revealed that N8 protonation is more favorable by 3.9 kcal mol-' (Terry Jones, personal communication).…”
Section: Structure Of the Rhdhfr5-deazafolate Binary Complexmentioning
confidence: 88%
“…Several investigators (5,7,27) have suggested that the strong interaction between MTX and DHFR is the result of the ionic reaction between the protonated MTX and the negatively charged Asp-27 in a hydrophobic environment. However, unless the charged group is stabilized by the protein surroundings, the energy gained by the ionic interactions would be lost for desolvating the charged groups.…”
Section: Free-energy Perturbation Methodsmentioning
confidence: 99%
“…If the total energy is written as Etot = Ebadh + Eele + EvdW, [5] where Ebadh represents the bond, the angle, and the dihedral AGAB = AGAA' + AGA'B- [7] In state A' the solute has the same bond, angle, dihedral, angle, and dihedral terms. This type of decomposition has been used, in earlier studies (25) on solvation of amino acid side chains, to overcome some sampling difficulties during the conversion of a polar solute to a nonpolar solute in water.…”
Section: Free-energy Perturbation Methodsmentioning
confidence: 99%
See 1 more Smart Citation